Effect of Secondary School Principals' Record-Keeping Practice on Administrative Effectiveness in Delta State, Nigeria - Ossai, A. G. (NIU Journal of Social Sciences, 2024)
This study's goal was to examine the effects of principals' record-keeping procedures on the management of public secondary schools in Delta State, Nigeria. The research design used in this study was descriptive. 473 public high school principals from the Delta region participated in the survey. By using stratified random sampling, 150 principals (100 men and 50 women) were selected as a sample. Two research questions and two hypotheses served as the foundation for conducting this investigation. A self-structured instrument titled “Principals Recording Keeping Practices for Enhanced Administrative Efficiency Questionnaire” (PRKPEAEQ), is the name of the instrument. Two professionals validated the scale. Internal consistency was assessed using Cronbach's alpha, and the two groups' reliability indices were 0.81 and 0.85, respectively. Utilizing the direct application method, the researcher(s) collaborated with three research assistants to gather the data. The study questions were answered using the mean and standard deviation, and a chi-square probability table was employed to assess the null hypotheses at the 0.05 level of significance. The results demonstrate that school administrators are using computers and cloud storage as management tools to enhance the efficiency of Delta Public Secondary Schools. The Ministry of Education should advise school administrators to use computers and cloud storage, among other things, according to the conclusions.